2016
DOI: 10.1002/ajoc.201600346
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Synthesis of 3‐Aryl‐3‐hydroxy‐2‐oxindole Derivatives by Using Water as the Solvent: Experimental and DFT Studies

Abstract: Ah ighly efficient catalyst-freeF riedel-Crafts reaction of isatin with phenol by using water as the solvent provided 3-hydroxy-2-oxindole derivatives in excellenty ields.DFT studies on variousm odel systems suggested that the catalytic role of water involved activation of the reactant throughh ydrogen-bonding interactions.Scheme1.Friedel-Crafts reaction between sesamol (1)and isatin (2).Supporting information, including 1 Ha nd 13 CNMR spectraf or all compounds,and the ORCID identification number(s) for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Kumar and co-workers discovered a green, efficient catalyst-free Friedel-Crafts reaction in water, using phenol derivatives 6 and substituted isatins 1 for the synthesis of 3-aryl-3-hydroxy-2oxindoles 7 with an excellent yield of 98% (Scheme 3). Density functional theory studies have confirmed that water acts as a catalyst by activating the reactants through hydrogen bonding interactions (Kumar et al, 2016). Scheme 3.…”
Section: Water As a Solventmentioning
confidence: 99%
“…Kumar and co-workers discovered a green, efficient catalyst-free Friedel-Crafts reaction in water, using phenol derivatives 6 and substituted isatins 1 for the synthesis of 3-aryl-3-hydroxy-2oxindoles 7 with an excellent yield of 98% (Scheme 3). Density functional theory studies have confirmed that water acts as a catalyst by activating the reactants through hydrogen bonding interactions (Kumar et al, 2016). Scheme 3.…”
Section: Water As a Solventmentioning
confidence: 99%
“…From the discussion in the last section one can see that for the rate-controlling step (step 1 in Scheme 3) of the water auxiliary mechanism, the assistant participation of water molecules can lower the free energy barrier of the direct proton transfer in the mechanism without water auxiliary and the reduced extent of ΔG ⧧ values increases as the number of water molecules increases from mono-to two-to tri-water clusters, that is, in general, the 3molecule water cluster model is more favorable than the 1molecule water model or the 2-molecule water model to a certain extent. Based on what Emamian et al 29 and Kumar et al 34 reported, it is suspected that the decrease in the free energy barrier in the water auxiliary process may be attributed to the alleviation of ring tension in transition states formed by water molecules and the active site of the reaction. From the optimized structures of transition states in systems assisted by three models of water clusters given in Figure 11, one can see that the values of key bond angles C−C−H and C−O−H all increase and the transition state changes from six-to eight-and ten-membered structures with the number of the auxiliary water molecules increasing from 1 to 2 to 3, indicating that the ring tension in transition-state structures also decreases in this order.…”
Section: Most Beneficial Water Cluster Model In Eachmentioning
confidence: 99%
“…Similarly, Jung and Marcus implemented the three-site water model to indicate that the hydrogen bondmediated lowering of the energy barrier was the key origin for the enhanced acceleration of the cycloaddition reaction between quadricyclane and dimethyl azodicarboxylate. 33 Also, there was a novel result reported by Kumar et al, 34 that is, the water molecules play vital roles in the entire reaction that it could greatly reduce the activation free energy barrier (ΔG ⧧ ), and it is shown that the six-water cluster model could much lower the energy barrier than the tri-water cluster. Nevertheless, a systematic computational investigation of the different water cluster models assisting the title reaction is still rather scarce hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…Next, to enhance the yield, solvent and base was replaced with ethanol and diethyl amine, respectively and reaction mixture was stirred at room temperature. After six hours, reaction ended-up as single spot and desired compound 3a was obtained in 88% yield [31][32][33][34][35]. Rest of the compounds 3b-5j were synthesized in good to excellent yield (78-96%) using the optimized reaction conditions of compound a3.…”
Section: Chemistrymentioning
confidence: 99%
“…After completion of reaction, ethanol was evaporated on rotary evaporator to half of its original volume and 15 ml of ice cold water was added to the reaction mixture. Resulting precipitates were filtered using vacuum filtration and twice washed with cold ethanol (2 × 10 ml), followed by diethyl ether (10 ml) and finally dried in oven at 45°C to get desired compounds 3a-5j [31][32][33][34][35]. Synthesized compounds were first characterized using non-spectral techniques like TLC and melting point and then by different spectral techniques like IR, 1 H NMR, 13 C NMR, ESI-MS and elemental analysis.…”
Section: General Procedures For the Synthesis Of 3a-5j Compounds Usingmentioning
confidence: 99%